যদ্যপি আমার গুরু - ছফা, আহমদ (ঢাকা : মাওলা ব্রাদার্স, 1998)
Autobiographical reminiscences of a Bengali author.
Donated By Akbar Ali Khan ; Donated by Sultan-uz Zaman Khan
In Bengali.
Keywords: Sofa, Ahmed; Authors, Bengali -- Bangladesh -- Biography; Bengali literature